Arbitrary optical potentials - Gan, Koon Siang (2014)
Here we demonstrate a self-correcting closed loop feedback system for the generation of phase holograms (kinoforms). We investigate the effectiveness of such a system for the production of smooth optical potentials for cold atom experiments.